The Influence Of Health Education On Mother's Knowledge About Stunting Prevention In Toddler Age Children: Literature Review - Aprilyawan, Grenda; Wibowo, Tri Suryo (Open Access Health Scientific Journal, 2024)
Background: Stunting is a condition of failure to thrive and chronic nutritional problems caused by inadequate nutritional intake due to providing food that is not in accordance with needs over a long period of time. Stunting in toddlers will have a bad impact if it is not addressed immediately. Stunting can be caused by several factors such as inadequate nutritional intake from the womb until the age of 2 years or the first 1000 days of birth, recurrent infections and low birth weight, as well as a lack of maternal knowledge.Methods: The research design in this article is a literature review, by searching several literature sources in the form of research journals and determining the journal as health education, maternal knowledge and stunting in children under five. The selected research journal summarizes the research design, research description, variables and research results.Results: Based on research results from several journals, there is a significant increase in maternal knowledge between before being given health education about stunting and after being given health education.Conclusion: Maternal knowledge has an important role in preventing stunting in children under five. Mothers who understand what stunting is can provide adequate nutritional intake for their toddlers to avoid stunting